Analysis of Consumption Behavior and Purchasing Power of Society in the Digital Era - Henri Pardamean; Wahyu Murti (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
This research aims to analyze consumption behavior and purchasing power of society in the digital era, focusing on the use of e-commerce platforms and digital payment methods. The study employs a purposive sampling method to select 150 respondents aged 18 and older, who have internet access and have transacted through digital platforms. Data collection involved online questionnaires and structured interviews. Correlation and regression analyses were conducted to evaluate relationships between digital transaction frequency and the purchasing power level. The results demonstrate a significant positive relationship between the frequency of digital transactions and the buying power level with a correlation coefficient of 0.65 (p  0.01). The findings reflect the changes in consumption behavior during the COVID-19 pandemic, where society increasingly relies on technology to meet their daily needs. This research is expected to serve as a reference for local governments in formulating more effective fiscal policies, particularly in managing Regional Original Income (PAD) to promote sustainable economic development and enhance the quality of life in Bandungan District.